Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3892/mmr.2012.787
|View full text |Cite
|
Sign up to set email alerts
|

Identification of up-regulated and down-regulated cis-natural antisense transcripts in the human B lymphoblastic cell line IM-9 after X-ray irradiation

Abstract: Abstract. Ionizing radiation (IR) causes DNA injury and induces multiple signal mechanisms, including the regulation of DNA repair, the cell cycle and gene expression through the activation of p53-related pathways. Cis-natural antisense transcripts (cis-NATs), which are transcribed from the DNA strand opposite to that for mRNA of the gene, are recognized as important regulators of gene expression in eukaryotic cells, but the effects on cis-NAT expression by IR are unknown to date. Therefore, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In addition, we detected the natural antisense RNAs of MDM2 and CDKN1A genes in human cell lines in a previous study (23). Therefore, in order to examine whether natural antisense RNAs are present within exosomes, the natural antisense RNAs of LRRC24, MDM2 and CDKN1A genes were examined by strand-specific RT-PCR as described in Materials and methods.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, we detected the natural antisense RNAs of MDM2 and CDKN1A genes in human cell lines in a previous study (23). Therefore, in order to examine whether natural antisense RNAs are present within exosomes, the natural antisense RNAs of LRRC24, MDM2 and CDKN1A genes were examined by strand-specific RT-PCR as described in Materials and methods.…”
Section: Resultsmentioning
confidence: 97%
“…Kohno et al discovered that the natural antisense RNA of LRRC24 gene was upregulated in the human CRC tissues, compared with normal colon tissues (19). Furthermore, we detected the natural antisense RNAs of MDM2 and CDKN1A genes in human B lymphoblastic cells in a previous study, and showed that their natural antisense RNAs were in the cytoplasm (23). In the present study, it was clarified that their intracellular natural antisense RNAs were enclosed within exosomes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lymphoblastoid cell lines (LCL), for example, have been used to investigate differences in the function of pathways involved in DNA repair and apoptosis (Veldwijk et al 2011, Chiba et al 2012). They have also been used to identify genetic determinants of pathways involved in the cytotoxic response to IR (Shukla and Dolan 2005, Hartford and Dolan 2007, Niu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Natural antisense transcripts (NATs) are known as one of gene expression regulators in eukaryotes [7]. In the past several years, the expression of NATs in mammals is reported [8,9]. In addition, investigation that the differential expressions of several NATs are induced during the process of liver development is made [10].…”
Section: Introductionmentioning
confidence: 99%